Lesbian brides: post-queer popular culture. Issue 3 (4th May 2017) - McNicholas Smith, Kate; Tyler, Imogen
Abstract: The last decade has witnessed a proliferation of lesbian representations in European and North American popular culture, particularly within television drama and broader celebrity culture. The abundance of "positive" and "ordinary" representations of lesbians is widely celebrated as signifying progress in queer struggles for social equality. Yet, as this article details, the terms of the visibility extended to lesbians within popular culture often affirm ideals of hetero-patriarchal, white femininity. Focusing on the visual and narrative registers within which lesbian romances are mediated within television drama, this article examines the emergence of what we describe as "the lesbian normal." Tracking the ways in which the lesbian normal is anchored in a longer history of "the normal gay, " it argues that the lesbian normal is indicative of the emergence of a broader post-feminist and post-queer popular culture, in which feminist and queer struggles are imagined as completed and belonging to the past. Post-queer popular culture is depoliticising in its effects, diminishing the critical potential of feminist and queer politics, and silencing the actually existing conditions of inequality, prejudice, and stigma that continue to shape lesbian lives.